Hematological Parameters and Hemozoin-Containing Leukocytes and Their Association with Disease Severity among Malaria Infected Children: A Cross-Sectional Study at Pawe General Hospital, Northwest Ethiopia - Birhanu, Muluken; Asres, Yaregal; Adissu, Wondimagegn; Yemane, Tilahun; Zemene, Endalew; Gedefaw, Lealem (Interdisciplinary Perspectives on Infectious Diseases, 2017)
Hematological parameter changes are the most common complications in malaria. We aimed to determine the hematological parameters and hemozoin-containing leukocytes and their association with disease severity in malaria infected children aged between 1 and 15 years. A facility-based cross-sectional study was conducted at Pawe General Hospital from July 31 to December 30, 2014. Demographic and clinical data were collected using structured questionnaire. Blood specimen was collected from each study participant for hematological investigations. Data were analyzed using SPSS version 20. The overall prevalence of anemia was 40.3%, most of which were mildly anemic. Leukocytosis was found in 15.4% of study participants. More than a fourth (27%) of the children had severe malaria. Hemozoin-containing monocytes and neutrophils were found in 80.1% and 58.9% of the study participants, respectively. Under-five years of age (AOR = 3.01, 95% CI: 1.83–7.39, P<0.001), leukocytosis (AOR = 3.20, 95% CI: 1.65–6.24, P=0.001), mean hemozoin-containing monocytes >5% (AOR = 6.26, 95% CI: 2.14–14.29, P<0.001), mean hemozoin-containing neutrophils >5% (AOR = 7.93, 95% CI: 3.09–16.86, P<0.001), and high density parasitemia (AOR = 1.90, 95% CI: 1.13–3.18, P=0.015) were associated with severe malaria. Hemozoin-containing leukocytes, leukocytosis, and other identified associated factors should be considered for proper management of children with severe malaria.